The Fluorescent Palette of DNA-Templated Silver Nanoclusters for Biological Applications - Yang, Min; Chen, Xu; Su, Yuan; Liu, Haiyan; Zhang, Hongxing; Li, Xiangyang; Xu, Wentao (Frontiers in Chemistry, 2020)
DNA-templated silver nanoclusters (DNA-Ag NCs), as emerging fluorophores, display superior optical performance since their size is close to the Fermi wavelength. The fluorescent emission of DNA-Ag NCs can cover the violet to near-infrared (NIR) region by varying the DNA sequences, lengths, and structures or by modifying the experimental conditions (e.g., pH, temperature, buffer, salt, reactants, metal ions, macromolecular polymers, or small molecules). Furthermore, DNA-Ag NCs possess unique features, including high fluorescence quantum yields and stability, biocompatibility, facile synthesis, and low toxicity. Their excellent photoluminescent brightness, photostability, and low toxicity are crucial as signal reporters for fluorescent probing and imaging. This paper briefly describes the classic synthesis method, as well as the mechanism and critical factors affecting fluorescent DNA-Ag NCs. Recent advances have been made regarding DNA-Ag NCs as fluorescent probes in sensing and imaging. Finally, the future application prospects and challenges of fluorescent DNA-Ag NCs are discussed considering the rising progress. More studies are required to understand the interaction between nanocluster and biological systems. In the foreseeable future, the new biosensors and functional devices will be invented based on the intriguing properties of well-designed DNA-Ag NCs and their composites.